(untitled) (Journal of the College of Education for Women, 2019)
Change the properties of the river hydrological and geomorphological during his career from its source to its mouth depending on the variables may be quick effect and short-term, addressed the study put the Tigris River geomorphological and hydrological and environmental in the city of Baghdad and found that most of the manifestations geomorphological indicate that the river enters the aging in the area were not so previously evidence suggests hydrological and environmental river that entered this stage long ago may be an extraordinary period. He found that the cross sections and locations of erosion and sedimentation size and type of flow patterns may change with moderate values to patterns with relatively abnormal values for the river.